The Construction of Kekeluargaan as an Indonesia’s Organizational Culture - Marko S Hermawan; Mark K Loo (Humaniora, 2019)
Indonesia has the largest economy in Southeast Asia and the seventh largest GDP in the world, yet little is known about Indonesia’s organizational culture. This paper develops a deep understanding of kekeluargaan (kinship), which derives from an anthropological and sociological epistemologies. The paper explores Javanese culture as the foundation of Indonesia’s business context. A qualitative and indigenous approach was designed to determine if the kekeluargaan norm exists in the Indonesian workplace today. Document analysis and semi-structured interviews were used to collect data. The findings show that the kekeluargaan norm acts as the foundation of Indonesia’s organisational culture; with, hormat (respect) and rukun (harmony). Three proposition are given to consider the importance of understanding kekeluargaan as a salient Indonesian organizational culture. The paper concludes managerial and theoretical implications to Indonesian business context.